0857 Factors Associated With Sleep Health Among Middle-aged And Older Adults. (27th May 2020) - Lorenz, R A; Auerbach, S L; Li, C; Chang, Y
Abstract: Introduction: The concept of Sleep Health (SH) was developed to provide a multidimensional framework consisting of characteristics of sleep that have been closely associated with physical and mental well-being. Identification of key factors associated with SH can identify targets for intervention for its improvement. This study aimed to identify factors related to SH among middle-aged and older adults. Methods: A valid Sleep Health Composite Measure was recently developed from the data of the 2014 Core Survey of the Health and Retirement Survey and was used to assess overall SH in middle-aged and older adults. Spearman's correlations, T-test, and Kruskal-Wallis tests were used to explore the association of SH with age, gender, self-rated health, chronic disease burden, disability, pain, and modifiable lifestyle behaviors (physical activity, smoking, alcohol, sleep medication). Results: Our sample included 6, 095 adults with mean age of 68 years (SD=10.1; range 50-99 years). The majority were female (59.7%) and white (77%). Correlations showed significant moderate associations between SH and self-rated health (r=.404), sleep medications (r=.390), pain (r=-.315). There were significant but small associations between vigorous activity (r=-.193), alcohol (r=.112), currently smoking (r=-.089) and SH. SH was significantly worse among women compared to men (t(6093)=6.996, p<0.001). Furthermore, SH scores were significantly different between middle-aged versus older adults (p<0.001); varying levels of self-rated health (p<0.001), number of chronic diseases (p<0.001), and degree of physical disability (p<0.001). Conclusion: These findings provide evidence of factors related to SH among middle-aged and older adults, providing targets for intervention to improve health in this population. Age-related differences in relation to SH indicate intervention tailored for middle-aged adults may improve health outcomes as they age. Future studies are warranted to extend these findings using multivariable statistical approaches. Support: This study was supported by the University at Buffalo Clinical and Translational Science Institute (CTSI) funded by the National Institutes of Health (Lorenz PI).